Effects of Plant Diversity, Vegetation Composition, and Habitat Type on Different Functional Trait Groups of Wild Bees in Rural Beijing. Issue 4 (29th June 2018) - Wu, Panlong; Axmacher, Jan C; Song, Xiao; Zhang, Xuzhu; Xu, Huanli; Chen, Chen; Yu, Zhenrong; Liu, Yunhui
Abstract: The loss of flower-rich habitats and agricultural intensification have resulted in significant losses of wild bee diversity from agricultural landscapes that is increasingly threatening the pollination of zoochorous agricultural crops and agricultural sustainability. However, the links of different wild bee functional trait groups with habitat types and plant resources in agricultural landscapes remain poorly understood, thus impeding the formulation of effective policies for bee conservation. We therefore analyzed how bees representing different functional groups responded to variations in habitat type, vegetation composition and plant diversity. Natural shrubland sustained the highest diversity in bees overall, in large-sized bees, solitary bees and belowground-nesting bees, while each habitat harbored unique species. In half of the functional bee groups, species were negatively linked to tree coverage and herb coverage, respectively, while plant diversity was positively related to all functional groups except large-sized bees and aboveground-nesting bees. Overall bee abundance was positively related to abundance of plants in the Sympetalae, and negatively related to abundance of plants in the Archichlamydeae. Different bee functional groups showed distinct preferences for different plant communities. In order to conserve the diversity of wild bees across functional groups to optimize associated pollination services, a diverse habitat mosaic, and particularly plant species in Sympetalae need to be promoted in agricultural landscapes. Future studies should aim to enhance our understanding of plant-pollinator associations and specific food requirement of different wild bee species for their effective conservation.